Synthesis And Characterization of Hydroxyapatite-Gibbsite - Ferry arifiadi; Kristanto Wahyudi; Ria Julyana Manullang; Nurhidayati Nurhidayati; Hasna Rofifah Novianti (Jurnal Keramik dan Gelas Indonesia, 2021)
Hydroxyapatite (HAp) is a material that is often used in biomedical applications. However, this material has poor mechanical properties so that its use is still limited and needs to be modified by adding other materials to obtain better mechanical properties. In this study, synthesis was carried out by adding gibbsite to HAp with variations in the ratio of HAp/gibsite (% by weight) and heating at 1200oC for 2 hours. The results obtained are HAp-Gibsite which has a change in the mineral phase and mechanical properties according to the ratio of HAp/Gibsite (% by weight). The mechanical properties of the sample increased with the addition of gibbsite up to 60% by weight with the best conditions achieved with the addition of 20% gibbsite, namely the compressive strength value of 227 Mpa and vicker hardness of 5.54 Gpa. The addition of gibbsite greater than 60% by weight tends to cause a decrease in the mechanical properties of the sample due to the more decomposition of HAp into -TCP and the effect of excess alumina which increases the porosity of the sample